Lipid Nanoparticles Potentiate CpG-Oligodeoxynucleotide-Based Vaccine for Influenza Virus - Shirai, Seiki; Shibuya, Meito; Kawai, Atsushi; Tamiya, Shigeyuki; Munakata, Lisa; Omata, Daiki; Suzuki, Ryo; Aoshi, Taiki; Yoshioka, Yasuo (Frontiers in Immunology, 2020)
Current influenza vaccines are generally effective against highly similar (homologous) strains, but their effectiveness decreases markedly against antigenically mismatched (heterologous) strains. One way of developing a universal influenza vaccine with a broader spectrum of protection is to use appropriate vaccine adjuvants to improve a vaccine’s effectiveness and change its immune properties. Oligodeoxynucleotides (ODNs) with unmethylated cytosine-phosphate-guanine (CpG) motifs (CpG ODNs), which are Toll-like-receptor 9 (TLR9) agonists, are among the most promising adjuvants and are already being used in humans. However, the development of novel delivery vehicles to improve adjuvant effects in vivo is highly desirable. Here, we assessed the potential of lipid nanoparticles (LNPs) as CpG ODN delivery vehicles in mice to augment the vaccine adjuvant effects of CpG ODN and enhance the protective spectrum of conventional influenza split vaccine (SV). In vitro, compared with CpG ODN, LNPs containing CpG ODNs (LNP-CpGs) induced significantly greater production of cytokines such as IL-12 p40 and IFN- by mouse dendritic cells (DCs) and significantly greater expression of the co-stimulatory molecules CD80 and CD86 on DCs. In addition, after subcutaneous administration in mice, compared with CpG ODN, LNP-CpGs enhanced the expression of CD80 and CD86 on plasmacytoid DCs in draining lymph nodes. LNP-CpGs given with SV from H1N1 influenza A virus improved T-cell responses and gave a stronger not only SV-specific but also heterologous-virus-strain-specific IgG2c response than CpG ODN. Furthermore, immunization with SV plus LNP-CpGs protected against not only homologous strain challenge but also heterologous and heterosubtypic strain challenge, whereas immunization with SV plus CpG ODNs protected against homologous strain challenge only. We therefore demonstrated that LNP-CpGs improved the adjuvant effects of CpG ODN and broadened the protective spectrum of SV against influenza virus. We expect that this strategy will be useful in developing adjuvant delivery vehicles and universal influenza vaccines.